(untitled) (Research, Society and Development, 2019)
The objective of this article was to investigate how the theme of the rational and sustainable use of water is experienced in terms of practical applicability, and how it is disseminated through actions, within the school context, in four elementary schools of Elementary School municipal school network, in the city of Pombal, located in the upper Paraíba hinterland. Methodologically, the research can be classified as exploratory, the approach follows a qualitative approach. The data collection instrument consisted of a structured questionnaire with 18 open questions, applied with the directors of the schools surveyed. From the results, it was possible to conclude that, despite the reality of water restriction and the constant lack of water in the daily school life, there is still no management focused on the efficient and sustainable use of water in these schools, where there is no feedback from finance and education secretariats for school managers in order to provide better control of water consumption in school buildings, as well as the lack of more efficient facilities and a more in-depth work with students, about the importance of the conscious and sustainable use of water.